Sleep quality in rheumatoid arthritis - Anil Kumar; Rohini Handa; Sundeep Kumar Upadhyaya; Sirinder Jit Gupta; Deepak Ramchandra Malgutte (Indian Journal of Rheumatology)
Background: Patients with rheumatoid arthritis (RA) often have sleep dysfunction. This may adversely impact quality of life. Despite being common, sleep dysfunction is uncommonly assessed in the clinic. No data on sleep quality in RA patients is available from India. In this study we examined the sleep quality and factors influencing it in Indian patients with RA. Methods: This cross-sectional study evaluated sleep quality in 110 patients with RA using the Pittsburgh sleep quality index (PSQI) or its validated Hindi version (PSQI-H). The risk of sleep apnea was assessed by the Berlin questionnaire while the assessment of pain and fatigue was done on a visual analogue scale (VAS). Disease activity was assessed by simplified disease activity index, functional disability was assessed by the health assessment questionnaire disability index-Centre for Rheumatic Diseases version, and quality of life was evaluated by World Health Organization quality of life-BREF (WHOQOL-BREF). Socioeconomic status was assessed by modified Kuppuswamy scale. Results: Sixty four percent of our patients with RA demonstrated poor sleep quality. The mean global PSQI score was of 6.41 ± 3.07 (range 1–17). A high risk of sleep apnea was present in 26% of the study population. The use of glucocorticoids, high risk of sleep apnea, high disease activity, pain VAS, fatigue VAS, and functional disability were more common in poor sleepers. Multivariate logistic regression analysis revealed that high risk of sleep apnea, fatigue, and poor physical health domain of WHOQOL-BREF were independent risk factors for poor sleep quality. Conclusions: Patients with RA had a high prevalence of poor sleep quality. High risk of sleep apnea, fatigue and physical health domain of WHOQOL-BREF were identified as independent predictors of poor sleep quality. Clinic evaluation of patients with RA should incorporate the domain of sleep quality.